Improving function of cytotoxic T‐lymphocytes by transforming growth factor‐β inhibitor in oral squamous cell carcinoma. Issue 10 (2nd August 2021) - Kondo, Yutaro; Suzuki, Susumu; Takahara, Taishi; Ono, Shoya; Goto, Mitsuo; Miyabe, Satoru; Sugita, Yoshihiko; Ogawa, Tetsuya; Ito, Hideaki; Satou, Akira; Tsuzuki, Toyonori; Yoshikawa, Kazuhiro; et al.
Abstract: Immunotherapy with immune‐checkpoint therapy has recently been used to treat oral squamous cell carcinomas (OSCCs). However, improvements in current immunotherapy are expected because response rates are limited. Transforming growth factor‐β (TGF‐β) creates an immunosuppressive tumor microenvironment (TME) by inducing the production of regulatory T‐cells (Tregs) and cancer‐associated fibroblasts and inhibiting the function of cytotoxic T‐lymphocytes (CTLs) and natural killer cells. TGF‐β may be an important target in the development of novel cancer immunotherapies. In this study, we investigated the suppressive effect of TGF‐β on CTL function in vitro using OSCC cell lines and their specific CTLs. Moreover, TGFB1 mRNA expression and T‐cell infiltration in 25 OSCC tissues were examined by in situ hybridization and multifluorescence immunohistochemistry. We found that TGF‐β suppressed the function of antigen‐specific CTLs in the priming and effector phases in vitro. Additionally, TGF‐β inhibitor effectively restored the CTL function, and TGFB1 mRNA was primarily expressed in the tumor invasive front. Interestingly, we found a significant negative correlation between TGFB1 mRNA expression and the CD8 + T‐cell/Treg ratio and between TGFB1 mRNA expression and the Ki‐67 expression in CD8 + T‐cells, indicating that TGF‐β also suppressed the function of CTLs in situ. Our findings suggest that the regulation of TGF‐β function restores the immunosuppressive TME to active status and is important for developing new immunotherapeutic strategies, such as a combination of immune‐checkpoint inhibitors and TGF‐β inhibitors, for OSCCs. Abstract : We found that, TGF‐β suppressed the function of antigen‐specific CTLs in the priming and effector phases in vitro. And, we found a significant negative correlation between TGFB1 mRNA expression and the CD8 + T‐cell/Treg ratio. Inhibition of TGF‐β restores the immunosuppressive TME to active status by a mechanism different from that of immune‐checkpoint inhibitors, suggesting that the combination of both may lead to a new therapeutic strategy for OSCCs.